ANALISIS EFEKTIVITAS MESIN THRES ANALISIS EFEKTIVITAS MESIN THRESHER DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) PADA PT. MURINI SAM SAM II - Yosua Adinata Sipahutar; Helmizar Helmizar; Zuliantoni Zuliantoni (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2026)
The palm oil industry in Indonesia plays a strategic role in the national economy. One of the important machines in the palm oil processing process is the thresher machine, which functions to separate loose fruit from the fruit bunches. This study aims to analyze the effectiveness of the Rotary Drum Stripper type thresher machine at PT. Murini Sam Sam II with a capacity of 30 tons per hour, using the Overall Equipment Effectiveness (OEE) method. The OEE method measures equipment performance based on three main parameters: Availability, Performance, and Quality. Data were collected through observations, interviews, and operational documentation during 10 days of observation (August 6–15, 2024). The analysis results showed an average Availability value of 90%, Performance of 82%, and Quality reaching 100%. The total OEE value was 73.8%, which is still below the world-class standard of 85%. The decrease in effectiveness was mainly due to variability in production speed. Therefore, improvements are needed in the aspects of preventive maintenance, operator training, and sustainable TPM implementation.